2012
DOI: 10.1103/physrevlett.108.038501
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Magnitude Clustering in an Aftershock Sequence of Nano- and Picoseismicity

Abstract: One of the hallmarks of our current understanding of seismicity as highlighted by the epidemic-type-aftershock sequence model is that the magnitudes of earthquakes are independent of one another and can be considered as randomly drawn from the Gutenberg-Richter distribution. This assumption forms the basis of many approaches for forecasting seismicity rates and hazard assessment. Recently, it has been suggested that the assumption of independent magnitudes is not valid. It was subsequently argued that this con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 43 publications
(60 reference statements)
2
25
1
Order By: Relevance
“…To summarize, this study provides evidence of magnitude clustering in space and time in different microseismic catalogs monitored in three different hydraulic fracture treatments associated with vastly different reservoirs. In contrast, another recent study showed no evidence of magnitude clustering in low magnitudeinduced seismicity that is unrelated to hydraulic fracturing [Davidsen et al, 2012]. This strongly suggests that the magnitude clustering we observe here is a consequence of the specific geometrical constraints of finely laminated shale gas and tight oil reservoirs.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…To summarize, this study provides evidence of magnitude clustering in space and time in different microseismic catalogs monitored in three different hydraulic fracture treatments associated with vastly different reservoirs. In contrast, another recent study showed no evidence of magnitude clustering in low magnitudeinduced seismicity that is unrelated to hydraulic fracturing [Davidsen et al, 2012]. This strongly suggests that the magnitude clustering we observe here is a consequence of the specific geometrical constraints of finely laminated shale gas and tight oil reservoirs.…”
Section: Discussioncontrasting
confidence: 87%
“…Here we investigate this question in the broader context of the statistical properties of microseismic activity associated with hydraulic fracturing. Our particular focus is on those properties relevant for forecasting seismicity rates and time‐dependent seismic hazard assessment, namely, magnitude clustering [ Davidsen and Green , ; Davidsen et al , ; Lippiello et al , ] as well as spatiotemporal clustering [ Davidsen and Kwiatek , ; Davidsen et al , ; Davidsen and Baiesi , ; Hainzl et al , ; Moradpour et al , ]. Specifically, we investigate the presence of clustering for three microseismic catalogs recorded at different sites where hydraulic fracturing was performed.…”
Section: Introductionmentioning
confidence: 99%
“…Before proceeding to the presentation of our results obtained from the OFC model, we note that concerning the correlations between magnitudes of subsequent earthquakes, there is a diversity of views in the literature. Such correlations, reported by Lippiello et al (2007Lippiello et al ( , 2008, have been later attributed (Davidsen and Green, 2011;Davidsen et al, 2012) to catalog incompleteness. In a subsequent publication, however, Lippiello et al (2012) made an analysis of two California regions with different levels of catalog accuracy and different lower magnitude thresholds, which convincingly indicated that the amplitude of correlations does not depend on catalog incompleteness.…”
Section: Interrelation Between the Fluctuations Of The Order Parametementioning
confidence: 80%
“…Analysis of some foreshocks has shown that they tend to relieve stress around the fault which is the same mechanism of main earthquake. An aftershock [48,49] is a smaller earthquake that occurs after a previous main earthquake, in the same area of the mainshock. Aftershocks are formed as the crust around the displaced fault plane adjusts to the effects of the mainshock.…”
Section: The Foreshock and Aftershock Behavior Of Our Modified Modelmentioning
confidence: 99%